2020
DOI: 10.1002/14651858.cd012871.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Cervical stitch (cerclage) in combination with other treatments for preventing spontaneous preterm birth in singleton pregnancies

Abstract: Cervical stitch (cerclage) in combination with other treatments for preventing spontaneous preterm birth in singleton pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 149 publications
0
11
1
1
Order By: Relevance
“…Most guidelines do not recommend the combination of more than two of the three therapeutic options (P, Pess and C). This is supported by a Cochrane review [ 42 ].…”
Section: Discussionmentioning
confidence: 69%
“…Most guidelines do not recommend the combination of more than two of the three therapeutic options (P, Pess and C). This is supported by a Cochrane review [ 42 ].…”
Section: Discussionmentioning
confidence: 69%
“…Despite the biologic plausibility of their utility, data supporting adjunct therapies are lacking, and current guidelines do not currently recommend use of adjuncts. 1,13,14,33 In the meta-analysis by Ehsa-nipoor et al with informed use of examination-indicated cerclage, there was significant clinical heterogeneity between included studies for use of adjunct therapies, including antibiotics, tocolytics, and bed rest, precluding extension of the findings to support a specific periprocedure approach for adjuncts. 10 In our study, we aimed to systematically review the literature to provide an updated evaluation of available data addressing the use of antibiotic or tocolytic adjuncts.…”
Section: Discussionmentioning
confidence: 99%
“…Another comparable therapy, the vaginal progesterone gel Crinone ® , has failed to receive FDA approval because its efficacy in preventing PTB was not significantly greater than a placebo [ 7 ]. Thus, there is opportunity for a pharmaceutical approach to provide an alternative to mechanical interventions such as a cervical cerclage or pessary [ 31 , 32 , 33 ].…”
Section: Impediments To Treat Ptbmentioning
confidence: 99%